A Review on the Relationships between Processing, Food Structure, and Rheological Properties of Plant‐Tissue‐Based Food Suspensions. Issue 3 (May 2014) - Moelants, Katlijn R.N.; Cardinaels, Ruth; Van, Sandy; Van, Ann M.; Moldenaers, Paula; Hendrickx, Marc E.
Abstract Nowadays, there is much interest in controlling the functional properties of processed fruit‐ and vegetable‐derived products, which has stimulated renewed research interest in process–structure–function relations. In this review, we focus on rheology as a functional property because of its importance during the entire production chain up to the moment of consumption and digestion. This review covers the literature of the past decade with respect to process–structure–rheology relations in plant‐tissue‐based food suspensions. It became clear that the structure of plant‐tissue‐based food suspensions, consisting of plant‐tissue‐based particles in an aqueous serum phase, is affected by many unit operations (for example, heat treatment) and that also the sequence of unit operations can have an effect on the final structural properties. Furthermore, particle concentration, particle size, and particle morphology were found to be key structural elements determining the rheological properties of these suspensions comprising low amounts of starch and serum pectin. Since the structure of plant‐tissue‐based products was shown to be changed during processing, rheological parameters of these products were simultaneously altered. Therefore, this review also comprises a discussion of the effect on rheological properties of the most relevant processing steps in the production of plant‐tissue‐based products. Linking changes in rheology due to processing with process‐induced alterations in structural characteristics turned out to be quite intricate. The current knowledge on process–structure–function relations can form the basis for future improved and novel food process and product design.